Climate Change's Effect on Wetland Micro, Small, and Medium-Sized Enterprises (MSMEs') Marketing in South Kalimantan - Yeni Susanty; Laila Refiana Said; Akhmad Supriyanto; Minarti Limantara (Cita Konsultindo Research Center, 2024)
This research examines the impact of climate change on the marketing of Micro, Small and Medium Enterprises (MSMEs) operating in the wetlands of South Kalimantan. Using a qualitative approach, the aim is to understand how the phenomenon of climate change affects the marketing aspects of MSMEs in the wetland areas of South Kalimantan. Data was collected through in-depth interviews and observations involving MSME actors and environmental experts. The research results found that climate change has an influence on wetland MSMEs in South Kalimantan, especially in terms of production and marketing strategies. Climate change can also reduce productivity and increase production costs, thereby impacting product prices and availability on the market. This research provides recommendations for policy makers to support MSMEs in facing climate change through inclusive and sustainable policies